2016
DOI: 10.1590/0001-3765201620140553
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose determines the method for quantification of DNA double strand breaks

Abstract: Ionizing radiation induces DNA double strand breaks (DSBs) that trigger phosphorylation of the histone protein H2AX (γH2AX). Immunofl uorescent staining visualizes formation of γH2AX foci, allowing their quantifi cation. This method, as opposed to Western blot assay and Flow cytometry, provides more accurate analysis, by showing exact position and intensity of fl uorescent signal in each single cell. In practice there are problems in quantifi cation of γH2AX. This paper is based on two issues: the determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Histone H2AX phosphorylation (γH2AX) can be triggered by DNA double-strand breaks (DSBs) [21]. When cellular DSBs occur, H2AX is rapidly phosphorylated in the damaged chromatin, and this activity is localized in nuclear foci [22].…”
Section: Decreased Pak2 Causes the Dna Damage In Early Embryosmentioning
confidence: 99%
“…Histone H2AX phosphorylation (γH2AX) can be triggered by DNA double-strand breaks (DSBs) [21]. When cellular DSBs occur, H2AX is rapidly phosphorylated in the damaged chromatin, and this activity is localized in nuclear foci [22].…”
Section: Decreased Pak2 Causes the Dna Damage In Early Embryosmentioning
confidence: 99%
“…According to Tanja Bulat’s study, foci was detected using Cellprofiler software, which automatically picks out foci within 6–30 pixels but did not include the foci over 30 pixels. 46 Thus, a high-resolution or confocal microscope could help to capture a more precise image, and proper counting strategies can provide more credible scores of γ-H2AX foci. 47 Irradiation has more than one way to induce DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, CQ combined with zinc could prevent NF-κB/P65 translocation to the nucleus and decrease the expression of several proteins encoded by NF-κB dependent genes. IR could induce various forms of DNA damage include breaking the bases and cleavage of the DNA backbone, resulting in DNA single strand breaks (SSBs) and double strand breaks (DSBs) [40]. γH2AX is a highly specific and sensitive molecular marker for monitoring both DSBs initiation and resolution [41].We found that phosphorylation of histone γH2AX was enhanced by combination treatment with CQ combined with zinc and 4 Gy compared with IR alone, suggesting that CQ combined with zinc might be blocking DNA damage-repair pathways induced by IR in CNE-2s cells.…”
Section: Discussionmentioning
confidence: 99%